2018
DOI: 10.1002/pola.29190
|View full text |Cite
|
Sign up to set email alerts
|

A structural reconsideration: Linear aliphatic or alicyclic hard segments for biodegradable thermoplastic polyurethanes?

Abstract: Thermoplastic polyurethane elastomers (TPUs) with a biodegradable chain extender and different nonaromatic diisocyanate hard segments were synthesized and tested concerning their thermal, mechanical, and degradation properties and for their processability regarding electrospinning. The design of the TPUs was based on the structural modification of the hard segment using linear aliphatic hexamethylene diisocyanate (HMDI), more rigid alicyclic 4,4′‐methylene bis(cyclohexylisocyanate) (H12MDI), 1,3‐bis(isocyanato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The structure of the aliphatic, aromatic, and/or ester ring group is in an isocyanate monomer. The hard segments (HS) are composed of isocyanates and chain extenders, which form stiff urethane units, and soft segments (SS) are based on aliphatic polyethers, polyesters, or polydimethylsiloxanes, named as macrodiols [20,21,22,23].…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the aliphatic, aromatic, and/or ester ring group is in an isocyanate monomer. The hard segments (HS) are composed of isocyanates and chain extenders, which form stiff urethane units, and soft segments (SS) are based on aliphatic polyethers, polyesters, or polydimethylsiloxanes, named as macrodiols [20,21,22,23].…”
Section: Methodsmentioning
confidence: 99%
“…As for the dominant component of PESU hard‐segment domain, isocyanate compounds exert an influence on PESU degradation first through the chemical structure. Generally speaking, PESU synthesized from aliphatic isocyanates (such as HDI) is more resistant than that from aromatic isocyanates (such as MDI) because the aliphatic chain is more flexible and easy to rearrange to form intermolecular hydrogen bonding . The increased density of cross‐linking points due to increasing isocyanate content would also result in the formation of more stable and compact network structure of PESU, which prevents water penetration of the bulk PU substance and blocks the reaction of ester groups with water.…”
Section: Biodegradable Pu Small‐diameter Vascular Scaffoldsmentioning
confidence: 99%
“…Currently studied biodegradable polymers do not meet all the requirements of biomedical and packaging applications, showing high brittleness or poor thermal and barrier properties 1–5 . Due to their tunable mechanical and degradation properties, thermoplastic polyurethanes (TPUs) are suitable for these applications 6–9 . TPUs with a wide range of physical–chemical and degradation properties may be obtained by varying not only the composition, molecular mass or the ratio between hard and soft segments but also synthesis and processing conditions, chemical structure and intermolecular interactions between segments 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic diisocyanates are preferred as hard segments in TPUs because the degradation of aromatic diisocyanates results in toxic amine‐derived products 8 . It was observed that isophorone diisocyanate (IPDI) and 4,4′‐methylene bis(cyclohexyl isocyanate) led to better mechanical properties of TPUs than hexamethylene diisocyanate (HMDI) 7 . In addition, medical grade polyurethanes were synthesized starting from lysine methyl ester diisocyanate and poly(ethylene oxide) (PEO) 9 …”
Section: Introductionmentioning
confidence: 99%